A New Technique to Compute Coupled Coincidence Points. (29th January 2014) - Jain, Manish; Gupta, Neetu; Kumar, Sanjay
Abstract : We compute coupled coincidence points without assuming the condition of compatibility of the pair of maps and relaxing the continuity condition of both the maps. In fact, our technique improves the technique introduced by Sintunavarat et al. (2011) which was then used by Hussain et al. (2012) to obtain coupled coincidence points.